A Feasible Review on Cloud Computing Security Services with Recent technologies used in the Digital Channels (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fog computing plays a significant role in the field of cloud computing. Fog computing is termed as decentralization of data in the cyber world. This paper mainly focused on the feasible review of fog computing security with services and threats in the digital channels. This paper aims to explore the feasible study of fog computing with existing technologies, devices, and services from various research points of view. It's also described the systematic review and fundamental of fog computing. This paper summarized various digital channel techniques with fog computing and security threats in cyber networks based on the fog.